The Correlation Analysis of Social and Economic Spendings, Economic Growth, and Poverty with Special Reference to West Java Province 2010 – 2013 - Sumiyarti Sumiyarti; Budi Santosa (International Journal of Small and Medium Enterprises and Business Sustainability, 2019)
This study aimed to examine the effects of social and economic expenditures on economic growth and poverty in regencies and cities in the provice of West Java by using a simple correlation analysis. In this analysis, the economic growth and poverty are simply formulated as variables that have correlations with social and economic spendings in each regions. The study has two important findings. First, the tendency of economic development and its policies in the majority of the regions is more oriented towards economic growth rather than poverty reduction. Second, the impacts of social and economic spendings on economic growth and poverty are more occurred in cities rather than in regencies.